2009
DOI: 10.1007/s10661-008-0728-1
|View full text |Cite
|
Sign up to set email alerts
|

Parallel factor analysis of fluorescence EEM spectra to identify THM precursors in lake waters

Abstract: Dissolved organic matter (DOM) can react with chlorine and yield undesirable disinfection byproducts (DBPs), e.g., trihalomethanes (THMs). Numerous studies have demonstrated that various DOM constituents have DBP formation potentials. We explored in this study the use of fluorescence excitation-emission (EEM) spectroscopy to identify THM precursors in 55 lakes in Missouri, USA. EEMs of the lake waters were decomposed into five factors of different origins through parallel factor analysis. The correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The concentrations of HM detected in the three locations under study were similar to those reported for the groundwater (Salameh et al 2002), in addition to rivers and estuaries (Christof et al 2002;Hua et al 2010). In the Valley of Mexico, although the generation of HM in the Xochimilco canals has been studied, it is not possible to compare the results because these were omitted from the preceding report (Mazari-Hiriart et al 2008).…”
Section: Concentration Of Hmsupporting
confidence: 85%
“…The concentrations of HM detected in the three locations under study were similar to those reported for the groundwater (Salameh et al 2002), in addition to rivers and estuaries (Christof et al 2002;Hua et al 2010). In the Valley of Mexico, although the generation of HM in the Xochimilco canals has been studied, it is not possible to compare the results because these were omitted from the preceding report (Mazari-Hiriart et al 2008).…”
Section: Concentration Of Hmsupporting
confidence: 85%
“…36,54,55 Previously all of these identified PARAFAC components have been found to correlate with regulated and unregulated DBPs precursors. [56][57][58][59] Thus their presence could indicate a risk for producing DBPs in chlorinated finished water.…”
Section: Comparison Of Feem Measurements Of Modified and Reference Bimentioning
confidence: 99%
“…Chromophoric DOM (CDOM) has been measured in a variety of lakes, providing a concentration proxy, degradation or diagenetic status, and inferred structural characterizations of bulk DOM (Cuthbert and del Giorgio 1992, McKnight et al 1997, Morris and Hargreaves 1997Wu et al 2003, Hua et al 2010, Yao et al 2011. More recently, fluorescence excitationemission matrix (EEM) techniques coupled with parallel factor (PARAFAC) analysis have been widely used to investigate characteristics of DOM in aquatic systems, including lake waters (Mostofa et al 2005, Wang et al 2007, Hiriart-Baer et al 2008, Fellman et al 2010, Osburn et al 2011, Yuan et al 2014, Zhao et al 2016.…”
Section: Introductionmentioning
confidence: 99%